Estudo da via de sinalização PI3K-Akt E GSK3β em carcinomas epidermoides metastáticos e não metastáticos de cavidade bucal - Matsuo, Flávia Sayuri (2015)
Oral squamous cell carcinoma (OSCC) represents more than 90% of all malignant neoplasms that affects these region. In most cases the diagnosis is detected in an advanced stage, hence the patient has a poor prognosis. Thus, studies with proteins that are involved in signaling pathways have been widely investigated as possible new therapeutic targets to aid the early diagnosis and prognosis. The PI3K-Akt signaling pathway has been prominent in the development of many types of tumors, including OSCC. One of the target proteins of this pathway is Akt, a serine/threonine protein kinase that is regulated by PI3K. Once phosphorylated, Akt is able to regulate multiple substrates causing metabolic disorders and activating cellular growth and proliferation. Therefore, this study aimed to investigate by immunohistochemistry the expression of Akt total, pAKT1-Thr308, pAKT-Ser473, GSK3β, pGSK3β-Ser9 e pmTOR2448 in 106 patients, being 16 controls and 90 OSCC patients, and their clinic-pathologic factors association. Additionally, this study also investigated Akt1/2/3, PIK3CA, mTOR e GSK3β gene expression in 23 patients, being 7 controls and 16 OSCC patients. All OSCC diagnoses were histologically confirmed and splitted in two groups: non-metastasizing (PNM) and metastasizing primary tumors (PM). The social and clinic-pathologic data were retrieved from each patient s medical files by using a semi-structured questionnaire. For immunohistochemistry proposal, it was performed a TMA technique and all proteins was revealed by the streptavidin-biotin peroxidase method. For gene expression, it was used the real time PCR approach. The immunohistochemical results showed that GSK3β, pGSK3β-Ser9, AKT total and pmTOR2448 proteins were more expressed in the OSCC group than the control one, suggesting these proteins can be related to OSCC development and progression. Furthermore, AKT total, pAKT1-Thr308, pAKT-Ser473, GSK3β and pGSK3β-Ser9 expression were related to the clinic-pathologic factors, including sex, family cancer history, localization, histological grade and metastasis. The GSK3β protein expression was higher in metastatic patients, therefore indicating to have a biomarker role in OSCC progression and metastasis. The correlation analysis showed significant positive correlation among investigated proteins, which means PI3K-Akt signaling pathway-driven OSCC development. The relative expression of all investigated genes was higher in the control group, except for AKT3 and GSK3β, but no significant differences was observed. The mTOR gene expression was significantly higher in the control group when compared to PNM and PM groups, suggesting such pathway to be somewhat complex and the necessity of further studies to elucidate its role in OSCC development and progression. In conclusion, these results indicate an activation of the PI3K-Akt signaling pathway in our OSCC sample and highlight a pivotal role for GSK3β protein as a prognostic biomarker and predictor of metastasis.